Monetary policy, accounting conservatism and trade credit - Bingbin Dai; Fan Yang (China Journal of Accounting Research, 2015)
Using a sample of A-share listed firms in China during the 2003-2012 period, this paper investigates the effect of accounting conservatism on trade credit, taking changes in monetary policy into account. We find that corporations with higher accounting conservatism obtain more trade credit and that accounting conservatism has a greater influence on trade credit under tight monetary policy. Furthermore, the backgrounds of the supplier and customer influence the positive relationship between accounting conservatism and trade credit. This influence is more evident when a company is privately owned and has greater market power, and less evident when the supplier or customer is the controlling shareholder.
Keywords: E52; G32; M41; 650; Monetary policy; Accounting conservatism; Trade credit